A paratesticular inflammatory myofibroblastic tumor and review of the literature - Ali Alkan; Serhat Toprak; Elif Berna Köksoy (Journal of Oncological Sciences, 2017)
Inflammatory Myofibroblastic tumor (IMT) is a pseudosarcomatous inflammatory lesion originating from soft tissue or viscera. It has been reported in different solid organs, rarely in genitourinary system. Thirty-eight year old male patient presented with scrotal pain and lump. Ultrasonography revealed a 4.5 × 3.5cm ovoid heterogeneous mass related with epididymis. Patient was treated with right orchiectomy and the pathology confirmed the diagnosis of paratesticular IMT. Our case had similar clinical and pathological characteristics with other cases in the literature. Although IMT has a benign nature, due to inadequate experience and possibility of recurrence in other organs, patients should be followed after surgical resection.